A utilização de normas de competência em julgamentos monocráticos e o artigo 557 do CPC - Virgolino, Pedro Sobrino Porto (2012)
The aim of this paper is to analyze the powers conferred by art. 557 of the CPC to the judgerapporteur and the compatibility of this legal tecnique with the principles and guarantees contained in the Charter of 1988. And also check if this dispositive is able to provide the speed required by the legislature. We traced the contours of the principle of collective judgment in the courts and the effect it produces in the interpretation of the jurisdictional rule laid down in art. 557. The research presents all hypotheses of singular decision contained in the article. 557 and the limits of the power of the judge- rapporteur. It´s defined the appropriateness of appeal against the decision of the judge-rapporteur, the procedure of trial of this feature and the applicability of the fine defined in § 2 of this article. The research was developed through the survey of the vast doctrinal material produced and judicial precedents regarding the article 557. Empirical research was conducted through sampling, regarding the judgments of appeal made by the Court of the State of Espirito Santo. As a result, it was possible to detect the art. 557 is not necessarily suitable technique to accelerate the process. It was also noted in several cases that the judge-rapporteur decision not strictly observe the limits of art.